Manhaj Periwayatan Hadis Daâif al-Bukhari serta Implikasinya terhadap Kedudukan Hadis sebagai Dalil Sharaâ (Kajian Metodologis terhadap Kitab al-Adab al-Mufrad) - Rakhman, Alwi Bani (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
It is interesting when the author of the best collection book of the hadith, al-Bukhari with his masterpiece al-Jami al-Sahih, a person who holds the highest status of hadith study, amir al-muâminin fi al-hadith narrated many daâif hadith which serve as hujjah. This is a literary study that focuses on the study of the book of al-Adab al-Mufrad by al-Bukhari. Based on documented data analysis of daif narrations of al-Bukhari contained in that book, there are some important points that bring us the following conclusions; al-Bukhari has several criterias in the transmission of daif hadith, namely 1) hadith is not mawdu hadith, 2) the content of hadith (matn) is on the same spirit with the sahihÂ hadith, 3) al-Bukhari tend to pay more attention on the quality of the content of hadith when narrated daâif hadith, 4) al-Bukhari prefer to choose transmitted hadith rather than logical opinion eventhough it is daâif hadith, and 5) Al-Bukhari didnât narate daâif hadith, except only for which its content has relation with fadail al-aâmal.Keywords: daâif hadith, al-adab al-mufrad, al-Bukhari